Bridging Across Disciplines: Understanding the Connections between Cultural Identity, Spirituality and Sociopolitical Development in Teaching for Transformation - Derise Tolliver; Elizabeth J. Tisdell (Adult Education Research Conference, 2002)
We briefly review and analyze the literature of several different disciplinary perspectives to understand the relationships between cultural identity, spirituality, sociopolitical development and their role in teaching for transformation.